Observer et analyser les dynamiques inclusives à l’œuvre dans un établissement d’enseignement supérieur : l’expérience « ACCESS Tertre » à l’Université de Nantes - Béatrice Chaudet; Sandrine Gelly-Guichoux; Arnold Magdelaine (Éducation et Socialisation)
This article focuses on "empowering" training and learning environments (TLE) (Fernagu Oudet, 2012) and on putting into perspective the conditions for the emergence of the inclusive dynamics inherent in them, on the scale of the Universityand, more specifically, of one of its university campuses. It is structured around three parts. The first part presents the inclusive dynamics imposed by the French regulatory context on higher education and research institutions. The second focuses on the emergence of an inter-service program called ACCESS. The third part presents the issues of understanding, appropriation and dissemination of an inclusive approach as revealed during the ACCESS Tertre project. This project is based on the production of an original map of the accessibility of the campus.